KEMANFAATAN BAHAN AJAR VIDEO PADA PELATIHAN JARAK JAUH CALON TUTOR IKM BDK JAKARTA - Suryadi, Asip; Berdiati, Ika; Qonitah, Laity; Mashum, Mahin Mahmud (Balai Diklat Keagamaan Jakarta, 2023)
Abstract This study describes the level of provision of participants' expectations of video instruction in BDK Jakarta Distance Training (PJJ). The study uses a mixed method with an explanatory design model. The model consists of two steps. The first stage is quantitative data collection and the second is qualitative data collection. The first step used an online survey and the second used in-depth interviews. Quantitative data were processed to find patterns of answers which would be followed up with in-depth interviews. The population was 27 online classes of PJJ participants with 40 for each. They are teachers, headmasters and supervisors of Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA) from Banten, DKI Jakarta and West Kalimantan. The online survey was conducted with all participants while in-depth interviews were conducted with a representative sample based on geography, positions (teacher, headmaster, supervisor) and education level (MI, MTs, MA). The research concludes that the number, information substance, duration and graphic aspect of video instruction in general, the respondents stated that it was sufficient, but many aspects still needed to be improved and adjusted. Because the research results confirm the high usefulness of video, it is recommended for training institutions to build on video instruction developers division so that the videos used meet the adequacy of quantity and quality. Abstrak Penelitian ini mendeskripsikan kemanfaatan dan tingkat pemenuhan harapan peserta terhadap bahan ajar video pada Pelatihan Jarak Jauh (PJJ) di BDK Jakarta. Metode yang digunakan adalah mix method pola explanatory sequential design. Populasi penelitian adalah alumni PJJ Calon Tutor IKM sebanyak 27 angkatan dengan masing-masing peserta setiap angkatan terdiri dari 40 guru, kepala madrasah dan pengawas dari tingkat Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs) dan Madrasah Aliyah (MA) di wilayah kerja BDK Jakarta yang terdiri dari provinsi Banten, DKI Jakarta dan Kalimantan Barat. Survei online dilakukan kepada seluruh peserta sedangkan in-depth interview dilakukan terhadap sampel representatif yang mewakili asal peserta, jabatan dan tingkat pendidikan (MI, MTs, MA). Penelitian menyimpulkan bahwa pada aspek jumlah, substansi informasi, durasi dan aspek grafis secara umum para responden menyatakan sudah memadai namun banyak aspek yang masih harus diperbaiki dan disesuaikan. Hasil penelitian merekomendasikan kepada lembaga pelatihan untuk meninjau kembali kebutuhan dan mutu video dan melembagakan pengembang bahan ajar video agar video yang digunakan memenuhi kecukupan jumlah dan mutunya.